Timely loss recognition and termination of unprofitable projects - Anup Srivastava; Shyam V. Sunder; Senyo Tse (China Journal of Accounting Research, 2015)
Ideally, firms should discontinue projects that become unprofitable. Managers, however, continue to operate such projects because of their limited employment horizons and empire-building motivations (Jensen, 1986; Ball, 2001). Prior studies suggest that timely loss recognition in accounting earnings enables lenders, shareholders, and boards of directors to identify unprofitable projects; thereby, enabling them to force managers to discontinue such projects before large value erosion occurs. However, this conjecture has not been tested empirically. Consistent with this notion, we find that timely loss recognition increases the likelihood of timely closures of unprofitable projects. Moreover, managers, by announcing late discontinuations of such projects, reveal their inability to select good projects and/or to contain losses, when projects turn unprofitable. Accordingly, thereafter, the fund providers and board of directors are likely to demand improved timeliness of loss recognition and stringent scrutiny of firms' capital expenditure plans. Consistently, we find that firms that announce large discontinuation losses reduce capital expenditures and improve timeliness of loss recognition in subsequent years. Our study provides evidence that timely loss reporting affects 'real' economic decisions and creates economic benefits.
Keywords: G14; G34; M41; 650; Timely loss recognition; Conditional conservatism; Agency costs; Corporate governance; Project discontinuations; Accounting quality